Demystifying Cryptography with OpenSSL 3.0 : Discover the Best Techniques to Enhance Your Network Security with OpenSSL 3. 0 - Khlebnikov, Alexei (Packt Publishing, Limited, 2022)
Use OpenSSL to add security features to your application, including cryptographically strong symmetric and asymmetric encryption, digital signatures, SSL/TLS connectivity, and PKI handling Key Features Secure your applications against common network security threats using OpenSSL Get to grips with the latest version of OpenSSL, its new features, and advantages Learn about PKI, cryptography, certificate authorities, and more using real-world examples Book Description Security and networking are essential features of software today. The modern internet is full of worms, Trojan horses, men-in-the-middle, and other threats. This is why maintaining security is more important than ever. OpenSSL is one of the most widely used and essential open source projects on the internet for this purpose. If you are a software developer, system administrator, network security engineer, or DevOps specialist, you've probably stumbled upon this toolset in the past - but how do you make the most out of it? With the help of this book, you will learn the most important features of OpenSSL, and gain insight into its full potential. This book contains step-by-step explanations of essential cryptography and network security concepts, as well as practical examples illustrating the usage of those concepts. You'll start by learning the basics, such as how to perform symmetric encryption and calculate message digests. Next, you will discover more about cryptography: MAC and HMAC, public and private keys, and digital signatures. As you progress, you will explore best practices for using X.509 certificates, public key infrastructure, and TLS connections. By the end of this book, you'll be able to use the most popular features of OpenSSL, allowing you to implement cryptography and TLS in your applications and network infrastructure. What you will learn Understand how to use symmetric cryptography Get to grips with message digests, MAC, and HMAC Discover asymmetric cryptography and digital signatures Focus on how to apply and use X.509 certificates Dive into TLS and its proper usage Manage advanced and special usages of TLS Find out how to run a mini certificate authority for your organization Who this book is for This book is for software developers, system administrators, DevOps specialists, network security engineers, and analysts, or anyone who wants to keep their applications and infrastructure secure. Software developers will learn how to use the OpenSSL library to empower their software with cryptography and TLS. DevOps professionals and sysadmins will learn how to work with cryptographic keys and certificates on the command line, and how to set up a mini-CA for their organization. A basic understanding of security and networking is required.